2008
DOI: 10.1002/bio.1057
|View full text |Cite
|
Sign up to set email alerts
|

Study on the interaction between palladium(II)–lincomycin chelate and erythosine by absorption, fluorescence and resonance Rayleigh scattering spectra and its analytical applications

Abstract: In pH 5.0-5.4 HAc-NaAc buffer solution, lincomycin (Linco) reacted with Pd(II) to form 1:1 cationic chelate, which could further react with erythrosine (Ery) to form 1:1 ion-association complexes (Pd-Linco)Ery. As a result, not only were the absorption and fluorescence spectra changed, but also the resonance Rayleigh scattering (RRS) intensity was greatly enhanced. These phenomena offered useful means for the determination of Linco by spectrophotometry, fluorescence and RRS methods. The linear range and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…(7) Resonance Rayleigh scattering (RRS) technique as an analytical method has received increasing interest due to its high sensitivity, convenience in performance, simplicity, and rapidity. Therefore, in recent years RRS method has been proposed for the determination of nucleic acids, (8)(9)(10) proteins, (11,12) inorganic ions, (13,14) pharmaceuticals, (15)(16)(17)(18)(19)(20) etc. These RRS techniques are usually based on the enhanced RRS signals resulting from binding of chromophoers to analytes; nevertheless the chromopores used, was synthetic porphyins, biological dyes, surfactants, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Resonance Rayleigh scattering (RRS) technique as an analytical method has received increasing interest due to its high sensitivity, convenience in performance, simplicity, and rapidity. Therefore, in recent years RRS method has been proposed for the determination of nucleic acids, (8)(9)(10) proteins, (11,12) inorganic ions, (13,14) pharmaceuticals, (15)(16)(17)(18)(19)(20) etc. These RRS techniques are usually based on the enhanced RRS signals resulting from binding of chromophoers to analytes; nevertheless the chromopores used, was synthetic porphyins, biological dyes, surfactants, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Resonance Rayleigh scattering (RRS), as a new analytical technique, is attracting more and more attention due to its high sensitivity and simplicity. In recent years, RRS has become an active research field of spectral analysis and has been widely applied to the study and determination of biological macromolecules such as nucleic acids, proteins, heparin, metal ions, nonmetal ions, and nanoparticle (Wang 2002), and it also shows good application prospect in medicine analysis (Qin et al 2009;Yi et al 2009). Flow injection analysis (FIA) technique is characterized by inexpensive yet highly flexible instrumentation, fast response, high sample throughput, and low consumption of reagents.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] Our experiments found that at room temperature and pH 4.6-5.3 Britton-Robinson (BR) buffer medium, Pd(II) reacted with PMZ to form 1:2 cationic chelate [Pd(PMZ) 2 ] 2þ , which further reacted with Na 2 WO 4 to form a 1:1 ternary ion-association complex ([Pd(PMZ) 2 ] Á (WO 4 )) and RRS, SOS, FDS were increased rapidly. The maximum RRS, SOS, and FDS wavelengths of ternary ion-association complex were located at 310 nm, 570 nm and 391 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%